(untitled) (GEOMATE Journal, 2025)
Based on the tsunami-prone zone map of Padang City, the Padang Barat sub-district is categorized as a High-Risk Zone. A tsunami in Padang City is predicted to occur within 20–30 minutes after a large-scale earthquake; therefore, it is necessary to analyze the distance and time parameters involved in the evacuation process to help residents estimate their ability to save themselves in the event of a tsunami. The research results identified 10 potential shelters in the Padang Barat sub-district, followed by an analysis of the time and distance parameters from the shoreline to each potential shelter. Based on the analysis, the fastest estimated time of arrival (ETA) is to the STBA Prayoga shelter, with a travel time of 2 minutes 30 seconds from the shoreline, while the longest ETA is to the SMPN 2 Padang shelter, with a travel time of 10 minutes 17 seconds. In the final stage, questionnaires were distributed throughout the Padang Barat sub-district. The analysis revealed that residents demonstrated good understanding and preparedness for evacuation during disasters. The Experience Indicator showed an achievement of 60.4%, the Knowledge Indicator was at 83.4%, and the Implementation Indicator stood at 59.5%. Although the Implementation Indicator was the lowest, overall, the community was considered well-prepared to face earthquake and tsunami threats.